1995
DOI: 10.1161/01.atv.15.4.441
|View full text |Cite
|
Sign up to set email alerts
|

Patients With Early-Onset Peripheral Vascular Disease Have Increased Levels of Autoantibodies Against Oxidized LDL

Abstract: Oxidative modification of LDL has been proposed as an early and crucial step in the development of atherosclerosis, and antibodies against such modified LDL are found in both healthy individuals and patients with atherosclerosis. In this study, 62 patients who were surgically treated for peripheral arterial occlusive disease below the age of 50 were investigated and compared with age- and sex-matched healthy individuals in a case-control study. Autoantibodies against oxidized LDL were measured with an enzyme-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
104
0
4

Year Published

1995
1995
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 243 publications
(110 citation statements)
references
References 29 publications
2
104
0
4
Order By: Relevance
“…We have recently made an investigation of antibodies against oxLDL in patients who were operated on because of severe peripheral atherosclerosis before the age of 50 years. In this study, the presence of antibodies discriminated better between the patients and healthy control individuals than any of the conventional risk factors smoking, hypertension and diabetes [53]. There are, however, also studies that fail to show any correlation between the antibodies and atherosclerosis [13,18], and the question of the pathogenic role ofthe antibodies is far from solved.…”
Section: Discussionmentioning
confidence: 58%
“…We have recently made an investigation of antibodies against oxLDL in patients who were operated on because of severe peripheral atherosclerosis before the age of 50 years. In this study, the presence of antibodies discriminated better between the patients and healthy control individuals than any of the conventional risk factors smoking, hypertension and diabetes [53]. There are, however, also studies that fail to show any correlation between the antibodies and atherosclerosis [13,18], and the question of the pathogenic role ofthe antibodies is far from solved.…”
Section: Discussionmentioning
confidence: 58%
“…10 Several studies demonstrated an increased titer of oxLDLAbs in patients with atherosclerotic coronary artery disease (CAD), 9,[11][12][13] acute myocardial infarction (MI), 14 and cerebral or peripheral artery disease. 15,16 In contrast, other studies found no such positive relationship between oxLDLAb titers and cardiovascular (CV) phenotypes. 17,18 Of interest, oxLDLAbs were detected in healthy individuals, 19 and a negative (inverse) association between total serum cholesterol and anti-OxLDLAb titers was reported in the general population.…”
mentioning
confidence: 93%
“…Circulating autoantibodies against oxidized LDLs are also abundant in humans and have been shown to correlate with severity of disease in cardiovascular patients. [13][14][15][16] These findings suggest the possibility of developing new treatments against atherosclerosis based on selective activation of atheroprotective immune responses against oxidized LDL antigens.Oxidation of LDL is associated with formation of reactive aldehydes, such as malondialdehyde (MDA), that form covalent adducts with lysine and histidine residues in apoB. 17,18 These haptenized peptide sequences become targets for the immune system.…”
mentioning
confidence: 95%
“…Circulating autoantibodies against oxidized LDLs are also abundant in humans and have been shown to correlate with severity of disease in cardiovascular patients. [13][14][15][16] These findings suggest the possibility of developing new treatments against atherosclerosis based on selective activation of atheroprotective immune responses against oxidized LDL antigens.…”
mentioning
confidence: 95%